2012
DOI: 10.3389/fphys.2012.00321
|View full text |Cite
|
Sign up to set email alerts
|

Functional enhancement of chitosan and nanoparticles in cell culture, tissue engineering, and pharmaceutical applications

Abstract: As a biomaterial, chitosan has been widely used in tissue engineering, wound healing, drug delivery, and other biomedical applications. It can be formulated in a variety of forms, such as powder, film, sphere, gel, and fiber. These features make chitosan an almost ideal biomaterial in cell culture applications, and cell cultures arguably constitute the most practical way to evaluate biocompatibility and biotoxicity. The advantages of cell cultures are that they can be performed under totally controlled environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 112 publications
(135 reference statements)
1
41
0
Order By: Relevance
“…That this view may be a little bit too simple has been brought to our attention by a thorough comparative study of the influence of three lipid-based transfection agents on hepatocytes focusing on various side effects on cellular metabolism presented in this issue of Archives of Toxicology (Böttger et al 2015). While this study confirmed the high efficiency of the tested transfection agents in silencing transcription of target genes by respective siRNAs together with a low cytotoxicity for the hepatocytes (Bakhshandeh et al 2012;Gao et al 2012), it demonstrated considerable effects on different aspects of lipid and amino acid metabolism of these cells (Böttger et al 2015). Using highly sophisticated shotgun lipidomics analysis, Böttger et al (2015) showed that all tested transfection agents altered the hepatocellular accumulation of triglycerides (two up and one down).…”
supporting
confidence: 56%
“…That this view may be a little bit too simple has been brought to our attention by a thorough comparative study of the influence of three lipid-based transfection agents on hepatocytes focusing on various side effects on cellular metabolism presented in this issue of Archives of Toxicology (Böttger et al 2015). While this study confirmed the high efficiency of the tested transfection agents in silencing transcription of target genes by respective siRNAs together with a low cytotoxicity for the hepatocytes (Bakhshandeh et al 2012;Gao et al 2012), it demonstrated considerable effects on different aspects of lipid and amino acid metabolism of these cells (Böttger et al 2015). Using highly sophisticated shotgun lipidomics analysis, Böttger et al (2015) showed that all tested transfection agents altered the hepatocellular accumulation of triglycerides (two up and one down).…”
supporting
confidence: 56%
“…Because of its versatility, chitosan was used extensively to coat metallic nanoparticles, including the ones used for hyperthermia applications [6,8], immobilization of enzymes on electrodes in electrochemical biosensors [9], drug delivery for administration of either biomacromolecules or low molecular weight drugs [10], etc. Chitosan is also considered an almost ideal biomaterial for cell culture applications, whereas the cell cultures model represent the most practical approach to evaluate biocompatibility and biotoxicity [11].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Moreover, CS can be molded in different forms, such as films, gels, sponges, fibers, nanoparticles, nanofibers; and combined with glycosaminoglycans (GAGs), such as chondroitin sulfate (ChS), can form sponges and scaffolds for diverse applications in tissue engineering. [5][6][7] ChS is an anionic polymer found as a natural GAG in the extracellular matrix (ECM) 8,9 typically of cartilage, skin, cornea, and the umbilical cord, and it is used in medicine for cartilage tissue engineering, in anti-inflammatory and antimicrobial devices, 10,11 and as a vehicle in pharmacological systems. 12 Furthermore, it shows activity in cell differentiation and proliferation.…”
Section: Introductionmentioning
confidence: 99%